We found a hat - Klassen, J. (Somerville, Massachusetts : Candlewick Press, 2016)
Two turtles find a hat that looks good on both of them, but, with fairness in mind, they decide to leave it be, until night falls and one of the turtles changes its mind.
Keywords: Hats -- Fiction; Turtles -- Fiction; Lost and found possessions -- Fiction; Hats -- Fiction; Turtles -- Fiction; Lost and found possessions -- Fiction